Serotonin receptor 1A-modulated phosphorylation of glycine receptor α3 controls breathing in mice - Manzke, Till; Niebert, Marcus; Koch, Uwe R.; Caley, Alex; Vogelgesang, Steffen; Hülsmann, Swen; Ponimaskin, Evgeni; Müller, Ulrike C.; Smart, Trevor G.; Harvey, Robert J.; Richter, Diethelm W. (The journal of clinical investigation, 2010)
Rhythmic breathing movements originate from a dispersed neuronal network in the medulla and pons. Here, we demonstrate that rhythmic activity of this respiratory network is affected by the phosphorylation status of the inhibitory glycine receptor α3 subtype (GlyRα3), which controls glutamatergic and glycinergic neuronal discharges, subject to serotonergic modulation.